Pickering emulsions as encapsulation means of bioactive compounds: review - Guevara-Guerrero, Beatriz; Beltrán, Carlos Andrés; Montero-Montero, Juan Carlos; Valdés-Restrepo, Magda Piedad (Revista Colombiana de Investigaciones Agroindustriales, 2022)
Identify the different technical aspects of Pickering emulsions, the importance and application of this technique in the food industry is the main objective of this bibliographic review., depending on the mechanical, physicochemical and stability properties that support food products. A variety of academic databases were used in this review such as Science Direct, Google Scholar, Scielo, Scopus, Elibro, amongst others. As a selection criterion, scientific articles, books, reviews and all the academic material related to the subject which were published since the year 2000 to the current year were taken into account. According to the sources consulted, it was found that this type of emulsion has great potential to be used in the production of dairy products, beverages, condiments and other areas of the food industry. In addition, there is a growing demand for products with biologically active food components in which those emulsions can be applied as encapsulating agents to help to preserving these components, which can bring nutritional and health benefits to consumers. However, further investigation of Pickering emulsions is still required to assess the delivery mechanism, release of bioactives and also compatibility with other components of real food systems.